Optische 3D-Konturerfassung und on-line Biegewinkelmessung mit dem Lichtschnittverfahren - Heckel, Werner (1995)
The aim of the thesis is the development of an in-process measurement of the bending angle in order to establish a control system for air bending. For fundamental investigations in configuration, calibration and evaluation a 3-D coordinate measuring system with flexible beam guiding system was built up. A strategy for automatic calibration based on the photogrammetric method of Direct Linear Transformation was developed. For in-process measurement of the bending angle a special tool (patent pending) was developed. The procedures for evaluation and calibration of the measuring system were adapted to the conditions in industrial use. The special tool allows in-process measurement of the bending angle both during every stage of the bending process and after release of the workpiece. The special tool allows direct control of the bending angle applying incremental correcting bends. The working accuracy achieves ± 0,2° regardless of the material properties. Every part turns out well after 1-3 correcting bends without any test bend